Continuous Miner And Roof Bolter Dust Control - Gerrit V. R. Goodman (The National Institute for Occupational Safety and Health (NIOSH), 2003)
In This Chapter [Design and operation of machine-mounted scrubbers Dust control with scrubbers and blowing ventilation Dust control with scrubbers and exhaust ventilation Dust control with exhaust ventilation and no scrubber Dust control methods common to all continuous miner sections Dust control for roof bolters] This chapter explains how to control dust at continuous miner sections in coal mines where the main dust sources are continuous miners and roof bolters. In relation to dust, there are three categories of continuous miner faces depending on the type of ventilation and whether or not a machine-mounted dust scrubber is used. These are— 1. Mining machines with dust scrubbers used with blowing face ventilation 2. Mining machines with dust scrubbers used with exhaust face ventilation 3. Mining machines without scrubbers used with exhaust face ventilation The approach to dust control is somewhat different in all three of these. However, there are many dust control features (such as the need to provide adequate airflow) common to all continuous miner sections. For workers at roof bolter faces, there are two dust sources: 1. Dust from the continuous miner when it is upwind. 2. A malfunctioning dust collector on the bolter, which allows dust to escape DESIGN AND OPERATION OF MACHINE-MOUNTED SCRUBBERS [Almost all new continuous miners are equipped with scrubbers. When the dust is excessive, it is possible that the scrubber needs some maintenance.]